Ethnomedical knowledge of plants used in alternative medicine to treat hemorrhoidal diseases in Lubumbashi, Haut-Katanga province, Southern Democratic Republic of Congo - Bashige Chiribagula Valentin; Okusa Ndjolo Philippe; Muhona Melman; Manya Mboni Henry; Bakari Amuri Salvius; Lumbu Simbi Jean Baptiste (BMC, 2024)
Abstract Background A variety of medicinal plants are used in traditional medicine in Lubumbashi for the management of hemorrhoidal diseases. However, no investigation has been conducted to gather the knowledge required for this type of management in the region. The present study was conducted to inventory the plants used in Lubumbashi to treat hemorrhoidal diseases and to relate their ethnomedical characteristics. Methods This study was conducted between March 2022 and February 2023 by interviews using semi-structured questionnaire with households (n = 1520), herbalists (n = 25), and traditional healers: THs (n = 59). Results The 1,604 respondents (sex ratio M/F = 0.9; mean age: 56 ± 3 years; experience: 12 ± 3 years) provided information on 100 taxa, 84 of which are used against internal hemorrhoids, Phyllanthus amarus being the most cited (Citation Index, CI: 0.76). Most of them are trees (38%) or shrubs (32%), belonging to 90 genera and 45 families dominated by the Fabaceae (10%) and Asteraceae (9%). They are indicated in 76 other pathologies, dominated by gastrointestinal disorders (GID), wounds and sexually transmitted infections (CI > 0.57). From these 100 taxa, 117 anti-hemorrhoidal formulations were derived, 11 of which combined more than one plant. In all these recipes, the leaf is the most commonly used part (> 60%) and the liniment (> 45%) is the most popular form of application. For the first time, this study reports 14 taxa as plants used in the treatment of hemorrhoids. Among these taxa, Ficus stuhlmannii, Ficus laurifolia, and Ocimum centraliafricanum are listed as medicinal plants for the first time. Khaya nyasica, and Syzygium cordatum, each with 11 uses, have the highest traditional medicinal value. Conclusion The findings of this study indicate that a significant number of medicinal plants are used in traditional medicine in Lubumbashi for the treatment of hemorrhoidal diseases. Some of these plants are endemic to the biodiversity area, while others are shared with other cultures and regions. A series of pharmacological studies is currently underway with the objective of validating the anti-hemorrhoidal properties of these plants and in order to identify phytochemical compounds responsible of this activity. Graphical Abstract